2012
DOI: 10.3109/01902148.2011.646052
|View full text |Cite
|
Sign up to set email alerts
|

The role of all-transretinoic acid in bleomycin-induced pulmonary fibrosis in mice

Abstract: Much evidence suggests that immune imbalance in the lung plays a crucial role in the development of pulmonary fibrosis. Recently, all-trans retinoic acid (ATRA) shifting the regulatory T/T-helper 17 (Treg/Th17) profile had been proven in some diseases. However, to date, the effect of ARTA of pulmonary fibrosis has not been examined from this aspect. The objective of this study was to study the effect of ATRA on bleomycin-induced pulmonary fibrosis in mice and its possible mechanism. Pulmonary fibrosis was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…It has been reported that ATRA might ease bleomycin-induced pulmonary fibrosis via inhibition expressions of interleukin (IL)-6 and transforming growth factor (TGF)-b (Dong et al, 2012). Moreover, amelioration of EF was observed after inhibiting IL family and TGF family member expression (Yan et al, 2013;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been reported that ATRA might ease bleomycin-induced pulmonary fibrosis via inhibition expressions of interleukin (IL)-6 and transforming growth factor (TGF)-b (Dong et al, 2012). Moreover, amelioration of EF was observed after inhibiting IL family and TGF family member expression (Yan et al, 2013;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…All-trans retinoic acid (ATRA) is a physiological metabolite of vitamin A that has a wide range of biological activities; it affects cell differentiation, proliferation, embryogenesis, inflammation and apoptosis (Dong et al, 2012;Datta and Lianos, 1999). It has been reported that ATRA might ease bleomycin-induced pulmonary fibrosis via inhibition expressions of interleukin (IL)-6 and transforming growth factor (TGF)-b (Dong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study [5 ]and other studies [6,7,8]have demonstrated a possible contribution for IL-17A in the development of pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 90%
“…4 Retinoic acid, as an active metabolite of vitamin A, includes all-trans retinoic acid (ATRA), 13-cis retinoic acid and 9-cis retinoic acid, and exerts various effects on physiological processes such as cell growth, differentiation, apoptosis and inflammation. 5 ATRA, as an important subgroup of retinoic acid, is a promising therapeutic agent for many diseases, such as acute promyelocytic leukemia, 6 pulmonary fibrosis, 7 renal interstitial fibrosis, 8 etc. In our previous study, we found that ATRA could achieve a similar effect to a RAAS inhibitor (benazepril) to prevent the progression of GS lesions in GS rats.…”
Section: Introductionmentioning
confidence: 99%